Model dinamika penyebaran pemilih dengan menggunakan pendekatan epidemiologi (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
In a world full of uncertainty, it is necessary to have scientific studies that can be used to predict various things in various fields of life that can help the government and stakeholders in making policies that are right on target. The predictions of this scientific study are built from a mathematical modeling. Mathematical modeling has been widely used in various fields, even in politics. One of the expected achievements of the mathematical model in the political field is that it can be used to see the dynamics of the distribution of voters in a presidential election. In the presidential and vice presidential elections, candidate pairs and their supporting parties play an important role in luring voters to vote for them on election day. Just as in an infectious disease that can spread and infect humans very quickly, presidential and vice presidential candidates can massively promote themselves through various means with the support of political parties to get as many votes as possible from the voters. In this study, a dynamic model of the distribution of voters will be built using an epidemiological approach. The model to be used is the SIR epidemic model. The model will use a system of differential equations involving three classes of voters, namely neutral voters who have not made their choice, voters who gravitate towards certain presidential and vice presidential candidate pairs, and voters who are apathetic. This model is expected to be used to predict the number of voters in a presidential election.
Keywords: mathematical modeling; population dynamics; epidemic model of SIR